Breaking the Hierarchy: Integrating Agile Leadership with Indonesian Cultural Values for Startup Resilience - Rosalina Puspa Tirta; Budi Santoso; Suwatno Suwatno (Yayasan Edukasi Cakrawala Nusantara, 2025)
Digital transformation and the VUCA business environment have created a demand for adaptive leadership models among Indonesian startups. While research on agile leadership has developed significantly globally, there remains a lack of integrated models that accommodate local cultural values in the context of early-stage startups in developing countries. This study aims to develop a contextual agile leadership integration model for Indonesian startups through a systematic literature review. Using the SPAR-4-SLR approach, we analyzed 82 high-quality articles from the Scopus database (2018-2025) through a combination of bibliometric and thematic methods. Results indicate a significant increase in post-pandemic publications with a terminological shift from adaptive leadership to agile leadership. Relational (41%) and execution agility (33%) emerged as dominant components, while implementation was most prevalent in technology and education sectors. Significant research gaps were identified, including minimal contextual models for Indonesian startups (only 6.7% of articles) and insufficient integration of local cultural values. The developed model provides a multi-dimensional framework that accommodates early-stage startup characteristics, Indonesian cultural values such as musyawarah and gotong royong, and phased implementation pathways. Theoretically, this model contributes to the development of leadership contingency theory in developing economy contexts. Practically, it offers concrete guidance for startup founders to adapt agile leadership practices according to business development stages, facilitating more effective product-market validation and adaptive strategic pivoting.